2022
DOI: 10.1029/2021jd036407
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Precipitation‐Recycling Process to the Wetting Trend in Xinjiang, China

Abstract: Xinjiang is located in inner Eurasia and is characterized by a typical mountain-basin system composed of "Three Mountains and Two Basins" (Figure 1). Its unique geographic location and topographic features result in a typical arid and semiarid climate that is highly sensitive to global climate change (Wu et al., 2010;Zhao et al., 2010). From the mid-1980s to 2000, the average annual air temperature increased by 0.7°C compared to that measured from 1961 to the mid-1980s in northwest China (Shi et al., 2006;Yao,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…For TS, both external moisture and internal evapotranspiration contribute positively to the increased precipitation. However, the deepening of the Central Asian trough facilitates the intensification of upward motion and guides more water vapor transport into TS (Ma et al., 2021; Zhang et al., 2022). Furthermore, the increase in evapotranspiration over TS is relatively limited compared to KL.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For TS, both external moisture and internal evapotranspiration contribute positively to the increased precipitation. However, the deepening of the Central Asian trough facilitates the intensification of upward motion and guides more water vapor transport into TS (Ma et al., 2021; Zhang et al., 2022). Furthermore, the increase in evapotranspiration over TS is relatively limited compared to KL.…”
Section: Resultsmentioning
confidence: 99%
“…The Modern‐Era Retrospective Analysis for Research and Applications, version 2 (MERRA2) is generated by NASA Global Modeling and Assimilation Office based on the Goddard Earth Observation System Model version 5, and offers products that cover a long‐term period from 1980 to the present (Gelaro et al., 2017). Previous studies have indicated that MERRA2 outperforms other reanalysis datasets in terms of accurately representing climate characteristics and long‐term patterns of water cycles in CA and northwestern China (Jiang et al., 2019; Ren et al., 2022; Zhang et al., 2022). We utilized the observed daily precipitation data from the China Meteorological Agency (CMA) to assess the accuracy of MERRA2 in Xinjiang, which exhibited overall consistency (Figure S2 in Supporting Information ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations